Internet Security : Professional Reference - Atkins, Derek [et al.] (New Dehli Techmedia, 1997)
If you are using the Internet to conduct professional or personal business, you want to know your Internet connection is secure. This book gives you all the information and tools you need to keep the hackers out and the mission-critical information in. It takes you through planning, implementing, and administering a secure Internet connection--from understanding UUCP and auditing to encryption and firewalls to understanding viruses. A comprehensive resource for security and network professionals alike, this book will show you how to use and implement the latest technologies in the most secure fashion, including Java, CGI, and Windows NT.
Includes Appendices and Index.
Keywords: Internet--Security Measures -- Computer Security